Pengetahuan Masyarakat Tentang Rabies Dalam Upaya Bali Bebas Rabies - Suartha, I Nyoman; Anthara, Made Suma; Putra, I Gusti Ngurah Narendra; Krisna Dewi, Ni Made Ritha; Mahardika, I Gusti Ngurah Kade (Buletin Veteriner Udayana, 2012)
This study aims to determine the level of public knowledge about rabies in an effort to Balirabies-free. The data were collected from three villages namely Kukuh in Tabananregency, Jagapati in Badung regency, and Seraya in Karangasem regency. The mentiontotal of responden are 991 people. Data were collected using questionnaire. Results showedthat respondents who do not know about the news that rabies has been in outbreak in Balias much as 33.3%. The sources of information about the disease of rabies came from themedia (TV, newspapers, radio) as much as 44%, and 31% from health extension program.First aid to do if bitten by a dog was wash wound with soap (80%), but there were alsoresponden who do not care for themself (4%). Most responden would go to health centerfor treatment (85%) if they were bitten by rabies dogs. But , there were also few respondenwho take no care and do nothing (7%). Public knowledge about the clinical symptoms of rabies was still low (53%), and as much as 39% of respondents did not know the signs ofrabies. Knowing of report place if there was an event of rabies or finding a dog with rabieswas to the head of the village (41%), to the Department of Animal Husbandry (39%) andnot reporting 4%. The conclusion of this study is the public knowledge about the disease ofrabies is moderate.
Keywords: Knowledge Society, Rabies, Bali